2015
DOI: 10.1111/tra.12272
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazine‐Derived Antipsychotic Drugs Inhibit Dynamin and Clathrin‐Mediated Endocytosis

Abstract: Chlorpromazine is a phenothiazine-derived antipsychotic drug (APD) that inhibits clathrin-mediated endocytosis (CME) in cells by an unknown mechanism. We examined whether its action and that of other APDs might be mediated by the GTPase activity of dynamin. Eight of eight phenothiazine-derived APDs inhibited dynamin I (dynI) in the 2-12 μM range, the most potent being trifluoperazine (IC 50 2.6 ± 0.7 μM). They also inhibited dynamin II (dynII) at similar concentrations. Typical and atypical APDs not based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
123
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 74 publications
2
123
0
1
Order By: Relevance
“…The mechanism involved could possibly be that this group of inhibitors block dynamin activity and inhibit endocytosis in tumor cells, as observed in HeLa and human neuroblastoma SH-Sy5Y cells [92]. Chlorpromazine marketed under the trade names Thorazine and Largactil among others, is a cationic amphiphilic phenothiazine-derived anti-psychotic drug which inhibits endocytosis by blocking dynamin 2 function [93]. Apart from above-noted dynamin inhibitors, chlorpromazine has been shown to have a relative high specificity for brain cancer [94, 95].…”
Section: Dynamin-targeted Inhibitors For Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism involved could possibly be that this group of inhibitors block dynamin activity and inhibit endocytosis in tumor cells, as observed in HeLa and human neuroblastoma SH-Sy5Y cells [92]. Chlorpromazine marketed under the trade names Thorazine and Largactil among others, is a cationic amphiphilic phenothiazine-derived anti-psychotic drug which inhibits endocytosis by blocking dynamin 2 function [93]. Apart from above-noted dynamin inhibitors, chlorpromazine has been shown to have a relative high specificity for brain cancer [94, 95].…”
Section: Dynamin-targeted Inhibitors For Cancer Treatmentmentioning
confidence: 99%
“…Moreover, it has been proven to inhibit glioblastoma growth in rat brains when used in combination with Nitrosureas. Phenothiazine-derived antipsychotic drugs (APDs), which are the cationic amphi-pathic drugs, also inhibit clathrin-mediated endocytosis [93]. It is proposed that potent dynamin inhibition is a shared characteristic of phenothiazine-derived APDs, but not other typical or atypical APDs [93].…”
Section: Dynamin-targeted Inhibitors For Cancer Treatmentmentioning
confidence: 99%
“…The uptake is blocked under these conditions (Figure B, Figure S14), suggesting that the proteins are taken up by the cells via an energy‐dependent pathway, involving either the clathrin‐mediated or caveolar endocytosis. As several proteins are transported via the clathrin‐mediated endocytosis (CME), we studied the uptake in the presence chlorpromazine (CPZ), a cationic amphipathic compound that inhibits the CME by depleting clathrin from the plasma membrane . As observed for SY, no inhibition of cellular uptake was observed in the presence of CPZ (Figure A,B, Figure S14), suggesting that a clathrin‐independent endocytosis (CIE) is probably responsible for the cellular uptake.…”
Section: Figurementioning
confidence: 87%
“…[32][33][34] Similarly, clathrin also mediated the internalization of CONPs. chlorpromazine, 35 the inhibitor of clathrin-mediated endocytosis, and wortmannin, 36 an indirect inhibitor of clathrin-mediated endocytosis, could improve cell viability of A375 cells in a dose-dependent manner. In line with the viability improvement, GF-AAS results indicated that chlorpromazine significantly reduced the content of intracellular Cu in A375 cells exposed to CONPs compared with control cells, which further validated clathrinmediated endocytosis is the major pathway of internalization for CONPs into melanoma cells.…”
Section: Discussionmentioning
confidence: 98%